2014
DOI: 10.7150/ijms.8647
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Regulation and Function of MicroRNAs in Multiple Sclerosis

Abstract: MicroRNAs (miRNAs) are single-stranded 19-25 nucleotide-long RNAs and have an important role in post-transcriptional gene silencing. It has been demonstrated that miRNAs are dysregulated in patients with multiple sclerosis (MS). For instance, miR-21, miR-142-3p, miR-146a, miR-146b, miR-155 and miR-326 were up-regulated in both peripheral blood mononuclear cells (PBMCs) and brain white matter lesions from MS patients and mouse model as well. These up-regulated miRNAs may be used as a signature for MS and play c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
143
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(153 citation statements)
references
References 58 publications
(97 reference statements)
2
143
1
3
Order By: Relevance
“…miRNA dysregulation has been associated with several chronic inflammatory diseases, such as inflammatory bowel disease (9), experimental autoimmune encephalomyelitis (10), multiple sclerosis (11), and rheumatoid arthritis (12). Lately, the enhanced expression of miR-21 (13) and miR-142 (14) was correlated with macrophage activation and encephalitis in the brain of SIV-infected rhesus macaques.…”
mentioning
confidence: 99%
“…miRNA dysregulation has been associated with several chronic inflammatory diseases, such as inflammatory bowel disease (9), experimental autoimmune encephalomyelitis (10), multiple sclerosis (11), and rheumatoid arthritis (12). Lately, the enhanced expression of miR-21 (13) and miR-142 (14) was correlated with macrophage activation and encephalitis in the brain of SIV-infected rhesus macaques.…”
mentioning
confidence: 99%
“…De acordo com Ma et al, (2014) a disfunção da barreira hematoencefálica é associada com a patogênese da EM. A down regulation do miR125a-5p está envolvida na regulação do efluxo de células imunológicas e na permeabilidade das células endoteliais na barreira hematoencefálica, sugerindo assim que o miR-125a-5p pode desempenhar um papel fundamental na fisiopatogênese da esclerose múltipla.…”
Section: Micrornas E Sncunclassified
“…Em um levantamento realizado por Ma et al (2014), foi descrito o mecanismo de ação dos miRNAs que estão desregulados em pacientes com esclerose múltipla, segundo estes os miRNAs possuem como função principal a regulação gênica de forma negativa. De acordo com esse estudo, diferentes microRNAs estariam interferindo na diferenciação dos linfócitos TCD4.…”
Section: Micrornas E Células Imunológicasunclassified
See 1 more Smart Citation
“…Mechanisms of transcriptional regulation that do not alter the sequence of DNA are called epigenetic regulations and have been studied extensively over the last few years. These studies have shown that epigenetics play a relevant role in a variety of diseases, e.g., IBD [4,5], multiple sclerosis [6], psoriasis [7] and systemic lupus erythematosus (SLE) [8]. Importantly, epigenetic marks may persist through cell division and are inheritable to next generations (long-term effects) [9].…”
Section: Introductionmentioning
confidence: 99%